What is the optimal duration of oral misoprostol treatment for cervical ripening?. (18th June 2017) - Drakopoulos, Panagiotis; Duyck, Céline; Gayet-Ageron, Angèle; Fernandez, Sonia; Irion, Olivier; Martinez de Tejada, Begoña
Abstract: Objectives : To evaluate the number of misoprostol tablets needed to obtain a Bishop score (BS) ≥ 6 or a significant cervical change (≥2 points in BS) during cervical ripening. Methods : Retrospective study of women with term singleton pregnancies and a BS < 6 taking oral misoprostol (20 μg first 2 doses followed by 40 μg every 2 h) for cervical ripening. Results : We included 400 women, 72% nulliparous, mean age of 31.3 ± 5.9 years and 70% with a baseline BS ≤ 2. During cervical ripening, 61 (15.3%) achieved a BS ≥ 6 and 205 (51.3%) a significant change in BS. The incremental risk to achieve a BS ≥ 6 after 4 tablets was low (+3.25%) with an incremental probability of +12.75% for painful uterine contractions and +0.5% for abnormal fetal tracing (AFT). The incremental probability to achieve a significant change in BS after 7 tablets was low (+2.0%). 24.3% women delivered by cesarean section which likelihood significantly increased with maternal age <35 years, BMI ≥ 30, nulliparity, AFT, and baseline BS ≤ 2. Conclusions : The marginal benefit of giving more than 7 misoprostol tablets (14 h) during cervical ripening is very low.